Vibration sensor placement for delamination detection in a beam structure based on the vibration-based chaotic oscillator method - Li, Xuan; Halim, Dunant; Liu, Xiaoling (2020)
This work aims to study the effect of sensor placement for delamination damage detection in a beam structure using a vibration-based chaotic oscillator method. A chaotic oscillator method is used due to its sensitivity to relatively small changes in measured vibration signal. The effect of vibration sensor placement to the delamination detection sensitivity for various delamination sizes is investigated. The Lyapunov Exponent (LE) is used in conjunction with the chaotic oscillator as a damage index to describe the extent of delamination damage in the laminated beam. The relationship between the damage index and sensor placement for different delamination size is studied to analyse the effect of sensor placement on detection performance. It is found that the sensor placement has a significant influence on the sensitivity of delamination detection with different delamination size.